IMPROVING PURCHASING DECISIONS THROUGH PERCEIVED FOOD QUALITY: AN SERVICE DOMINANT LOGIC (SDL) APPROACH - Lusi Suwandari; Monica Rosiana; Widiya Avianti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This study aimed to investigate the impact of visual and verbal packaging on purchasing choices by assessing the perceived quality of food. One hundred seventy-five respondents were surveyed, specifically consumers who purchase MSME food goods in Banyumas Regency, including food, beverages, crafts, and other packaged items. This study employs AMOS structural equation modelling to examine the proposed research model. The findings indicate that visual and verbal packaging benefits the perceived quality of food and influences consumers' purchasing choices. The variable of perceived food quality has a beneficial influence on purchase decisions and can operate as a mediator between visual and verbal packaging regarding buying decisions. The model is grounded in the Service's Dominant logic and the consumption value theory. According to this theory, consumer behaviour is influenced by cognitive and hedonic evaluations that stem from consumption experiences. These experiences highlight the active involvement of consumers in creating value during their interactions with products, including visual packaging, verbal packaging, and perceived food quality.